Browse over 20 million
homework answers & study documents

Mathematics

If 〖(1+x+x^2)〗^n = a_0+a_2 x^2+ ------ +a_2n x^2n then prove that a_0+a_3+a_6+ ----- = 3^(n-1).

Type

Homework

Rating

Showing Page:
1/2

Sign up to view the full document!

lock_open Sign Up

Sign up to view the full document!

lock_open Sign Up

Unformatted Attachment Preview

Answer on Question #44096, Math, Complex AnalysisProblem 1.2 = 2 4 = 1 Solution 1. + 2 + 2+ sin 2) , = 0,1.2 = 2 (cos ( ) + sin ( )) = 2 (cos 22222When = 0 : 2 = 2 (cos ( ) + sin ( )) = 2 4 .44On the other hand, 1 = 2 (cos ( ) + sin ( )) = 2 4 .44Problem 2.w^2= (-1+sqrt3 i)/2Solution 2.2 =1+3;2assume that = + ...
Purchase document to see full attachment

Anonymous
Outstanding. Studypool always delivers quality work.

Anonymous
Thanks for the help.

Anonymous
<3 it, thanks for saving me time.

Studypool
4.7
Trustpilot
4.5
Sitejabber
4.4